Phenotyping of tumor-associated macrophages in colorectal cancer: Impact on single cell invasion (tumor budding) and clinicopathological outcome - Koelzer, Viktor H. (Oncoimmunology, 2015)
Tumor-associated macrophages (TAM) play a controversial role in epithelial–mesenchymal transition (EMT) and prognosis of colorectal cancer (CRC). In particular, the microlocalization, polarization and prognostic impact of TAM in the immediate environment of invading CRC cells has not yet been established. To address this clinically relevant question, intraepithelial (iCD68) and stromal macrophages (sCD68), M1-macrophages (iNOS), M2-macrophages (CD163), cytokeratin-positive cancer cells (tumor buds) and expression of the anti-phagocytic marker CD47 were investigated in primary tumors of 205 well-characterized CRC patients. Cell-to-cell contacts between tumor buds and TAM were detected using high-resolution digital scans. The composition of the tumor microenvironment was analyzed with clinicopathological and molecular features. High CD68 counts predicted long term overall survival independent of microlocalization (iCD68 p=0.0016; sCD68 p=0.03), pT, pN, pM and post-operative therapy. CD68 infiltration correlated with significantly less tumor budding (iCD68 p=0.0066; sCD68 p=0.0091) and absence of lymph node metastasis (sCD68 p=0.0286). Cell-to-cell contact of sCD68 and invading cancer cells was frequent and ameliorated the detrimental prognostic effect of the tumor budding phenotype. Subgroup analysis identified long-term survival with CD47 loss and predominance of CD163(+) M2 macrophages (p = 0.0366). CD163(+) macrophages represented 40% of the total population, and positively correlated with total CD68 macrophage numbers (r[CD68/CD163] = 0.32; p = 0.0001). Strong CD163 infiltration predicted lower tumor grade (p = 0.0026) and less lymph node metastasis (p = 0.0056). This study provides direct morphological evidence of an interaction between TAM and infiltrating cancer cells. The prognostic impact of TAM is modulated by phenotype, microlocalization and the expression of anti-phagocytic markers in CRC.